The Forced Oscillation Test in the Diagnosis of Obstructive Ventilation Disorders in Pulmonary Tuberculosis Patients - E. M. Zhukovа; L. G. Vokhminovа (Туберкулез и болезни лёгких)
Clinical testing of the forced oscillation test (FOT) yielded criteria for bronchial obstruction: an increase in viscous respiratory resistance (VRR) (Rfo, Rin, Rex); the frequency dependence of VRR. The study of VRR promoted detection of bronchial malpatency in additional 20% of pulmonary tuberculosis patients who had no lung ventilation disorders, as evidenced by spirometry.